2020
DOI: 10.1017/s1431927620000021
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Morphological Features of Syrinx in Male Domestic FowlGallus gallus domesticusand Male Domestic PigeonColumba livia domestica: A Histochemical, Ultrastructural, Scanning Electron Microscopic and Morphometrical Study

Abstract: Many studies have been carried out to investigate the morphological structure of the syrinx in many bird species. However, the cellular organization of the syrinx in the fowls and pigeons is still unclear. The current study revealed that in fowl and pigeon, the syrinx is formed of three main parts including tympanum (cranial) part, intermediate syringeal part, and bronchosyringeal (caudal) part, in addition to pessulus and tympaniform membranes. A great variation in the structural characteristics of syrinx of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…For example, mast cells are observed along the lamina propria–submucosa under the tympanum epithelium. Also, the mast cells are recorded in fowls syrinx in our previous study (Ibrahim et al, 2020). Marshall & Dawicki (2007) found that these cells play an important role in tissue microenvironment as they released several mediators.…”
Section: Discussion and Summarymentioning
confidence: 88%
See 1 more Smart Citation
“…For example, mast cells are observed along the lamina propria–submucosa under the tympanum epithelium. Also, the mast cells are recorded in fowls syrinx in our previous study (Ibrahim et al, 2020). Marshall & Dawicki (2007) found that these cells play an important role in tissue microenvironment as they released several mediators.…”
Section: Discussion and Summarymentioning
confidence: 88%
“…The histological features of the syrinx have been described in several bird species by many authors (Yildiz et al, 2003(Yildiz et al, , 2005Frank et al, 2007;Yilmaz et al, 2012;Keskin & Ili, 2013;Ibrahim et al, 2020). However, the cellular elements and the fine structure of the budgerigar syrinx are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Tympaniform membranes lateral are functional membranes that produce melodic sounds in the Psittacidae family. 29 The development of the tympaniform membranes lateral is triggered by the development of the chirping sound. The rapid development that occurs in pubertal birds will then decrease gradually at aged 9 mo.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, TCs were identified as a novel type of interstitial cells and have been described in various organs of different vertebrates, especially in the human and rodents ( Cretoiu and Popescu, 2014 ). In birds, TCs were also observed in several organs, such as ileum, spleen, trachea, oviduct, and syrinx ( Yang et al., 2015 , 2017 ; Ibrahim et al., 2020 ; Mokhtar and Hussien, 2020 ; Mustafa and El-Desoky, 2020 ). These studies have demonstrated that the morphological characteristics of avian TCs are similar to those of other animal organs.…”
Section: Discussionmentioning
confidence: 99%
“…Avian TCs made up frequently close contacts with neighboring cell types/structures, such as immune cells (including mast cells and macrophages), smooth muscle cells, nerve fibers and blood vessels. Based on the appearance of direct homocellular contacts between Tps (Tps with Tps, Tps with cell bodies), heterocellular contacts between Tps and neighboring cell types/structures, and the release of shedding vesicles (including exosomes), which act as molecular complex intercellular signaling organelles, avian TCs may be implicated in intercellular signaling ( Ibrahim et al., 2020 ). Subsequently, avian TCs were suggested to regulate the physiological functions of surrounding cell types by direct/indirect contacts and shedding vesicles.…”
Section: Discussionmentioning
confidence: 99%